Analysis of Environmental Factors and the Efficacy of Teaching Methods in Training Institutions for Enhancing Human Resources Competency - Fanggidae, Rolland E.; Nursiani, Ni Putu; Salean, Debriana Y.; Molidya, Aldarine; Pong, Nekkidin (Universitas Pendidikan Ganesha, 2025)
This study addresses the lack of integrated analysis on how environmental factors and teaching methods jointly influence the effectiveness of vocational training in enhancing human resource competencies, particularly in the context of Kupang City. Using a mixed-methods approach, the research combined quantitative surveys of 150 participants with qualitative interviews and field observations at two training institutions to explore how physical, psychological, and social learning environments interact with instructional strategies. Data analysis through correlation and multiple regression revealed that both environmental factors and teaching methods significantly contributed to competency improvement, explaining 65% of the observed variance. Qualitative findings reinforced these results, highlighting how participatory teaching, use of digital tools, and a supportive learning atmosphere enhanced engagement, knowledge absorption, and even post-training income levels. The study concludes that both environmental quality and teaching methodology are not peripheral but central to the success of training programs. It recommends routine environmental audits, adoption of experiential and blended learning models, and facilitator upskilling through certification programs to sustain and scale the impact of training initiatives. These findings offer practical implications for institutions and policymakers in designing more effective and responsive training systems in resource-limited settings.